2009
DOI: 10.1289/ehp.0800153
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence among Former Love Canal Residents

Abstract: Background The Love Canal was a rectangular 16-acre, 10-ft-deep chemical waste landfill situated in a residential neighborhood in Niagara Falls, New York. This seriously contaminated site came to public attention in 1978. Only one prior study examined cancer incidence in former residents of the Love Canal neighborhood (LC). Objective In this study we aimed to describe cancer incidence in former LC residents from 1979 to 1996 and to investigate whether it differs from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Some of the ten articles on bladder cancer considered in the present review reported the presence of contaminants associated with bladder cancer in the study areas. Heavy metals in soil and groundwater, and β-HCH in blood of some residents were reported in the Sacco river areas [31]; hexachlorocyclohexanes, benzylchlorides, organic sulfur compounds, chlorobenzenes, and sodium sulfide/sulfhydrates polluted the Love Canal site [36], where a biomonitoring study reported also trichlorobenzene and dichlorobenzene contamination [37]. Dioxins were detected in biomonitoring studies in Campania waste sites [34] located in towns where increased bladder cancer risk was reported [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the ten articles on bladder cancer considered in the present review reported the presence of contaminants associated with bladder cancer in the study areas. Heavy metals in soil and groundwater, and β-HCH in blood of some residents were reported in the Sacco river areas [31]; hexachlorocyclohexanes, benzylchlorides, organic sulfur compounds, chlorobenzenes, and sodium sulfide/sulfhydrates polluted the Love Canal site [36], where a biomonitoring study reported also trichlorobenzene and dichlorobenzene contamination [37]. Dioxins were detected in biomonitoring studies in Campania waste sites [34] located in towns where increased bladder cancer risk was reported [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies suggest that living near a dump site may increase the incidence of cancer [3][4][5] and others found no association. [6][7][8][9][10][11] This inconsistency has also been stated in three reviews about the health of populations living close to toxic waste sites from the 2000s. [12][13][14] It has been previously hypothesized that landfill exposures are associated with increased incidence of leukemia and cancers of the urinary tract, bladder, kidneys, liver, biliary ducts, brain, lungs, rectum, and stomach.…”
Section: Pukkala Cancer Incidence Among Former Finnish Dump Site Resimentioning
confidence: 96%
“…Recently, increasing evidence has shown associations between living near industrially contaminated sites or being exposed to industrial air pollution and increased total cancer incidence and mortality [27][28][29][30]. Although the main focus has been on lung cancer [28,29,31,32], the increased risks have also been documented for kidney [33,34], bladder [31][32][33][34], and breast cancer [35][36][37] as well as leukaemia [33,[38][39][40] and non-Hodgkin's lymphoma [33,41,42]. Less evidence has been reported on prostate [43], colorectal [44], liver [31], and paediatric cancer risk [45,46].…”
Section: Introductionmentioning
confidence: 99%